Biomaterials in periodontal osseous defects - Nand Lal; Jaya Dixit (Elsevier, 2012)
ABSTRACT: Introduction: Osseous defects in periodontal diseases require osseous grafts and guided tissue regeneration (GTR) using barrier membranes. The present study was undertaken with the objectives to clinically evaluate the osteogenic potential of hydroxyapatite (HA), cissus quadrangularis (CQ), and oxidized cellulose membrane (OCM) and compare with normal bone healing. Materials and Methods: Twenty subjects with periodontitis in the age group ranging from 20 years to 40 years were selected from our outpatient department on the basis of presence of deep periodontal pockets, clinical probing depth ≥5 mm, vertical osseous defects obvious on radiograph and two- or three-walled involvement seen on surgical exposure. Infrabony defects were randomly divided into four groups on the basis of treatment to be executed, such that each group comprised 5 defects. Group I was control, II received HA, III received CQ and IV received OCM. Probing depth and attachment level were measured at regular months after surgery. Defects were re-exposed using crevicular incisions at 6 months. Results: There was gradual reduction in the mean probing pocket depth in all groups, but highly significant in the site treated with HA. Gain in attachment level was higher in sites treated with HA, 3.2 mm at 6 months. Conclusion: Hydroxyapatite and OCM showed good reduction in pocket depth, attachment level gain and osseous defect fill. Further study should be conducted by using a combination of HA and OCM in periodontal osseous defects with growth factors and stem cells.